Christiane Taubira – Honorary Doctorate in Laws and Human Rights : Discours d’acceptation - (:unkn) unknown (My University, 2016)
Former French Minister of Justice and Keeper of the Seals Christiane Taubira received an Honorary Doctorate in Laws and Human Rights at UWM on Jan. 30, 2016. Taubira insisted in her reception speech that everyone “maintain a constant vigilance” when it comes to human rights.Taubira served as France’s justice minister from 2012 until Jan. 27, 2016, when she resigned over a major political disagreement with the government's response to the November 2015 terrorist attacks in Paris.“We are going through a difficult period,” Taubira told about 50 guests gathered for the ceremony at the American Geographical Society Library. “We are confronted with serious disturbances, chaos in certain parts of the world [....] We must understand one another and bring a return to reason [....] and understand our intellectual resources, the resources of our energy and will, the resources of our imagination.”
Keywords: Christiane Taubira; Law; Human Rights; University of Wisconsin-Milwaukee